Larval and Larval Case Morphology of Hyposmocoma Species (Lepidoptera: Cosmopterigidae), With a Discussion on Adaptations to Larval Case-Bearing Locomotion. (18th September 2015) - Dupont, S.; Rubinoff, D.
Abstract : Terrestrial invasions of the aquatic environment are evolutionarily rare and involve significant morphological and behavioral adaptations. The Hawaiian endemic moth genus Hyposmocoma have truly amphibious larvae, and the genus has several convergent examples of adaptations to an aquatic environment. The study of a terrestrial species, Hyposmocoma ochrociliata Walsingham, and an aquatic species, Hyposmocoma kahamanoa Schmitz and Rubinoff, provides a template for understanding how general larval morphology, including chaetotaxy, exterior larval friction pads, thoracic legs, and extrinsic leg musculature, might impact significant ecological adaptations in the genus. The case diversity of Hyposmocoma is summarized and a detailed study of the burrito and cone type cases is discussed. The general larval morphology between the two studied species is not large, and we observed only slight differences in chaetotaxy, friction pad location, and thoracic sclerotizations. We suggest that the differences in friction pad placement on the larval body are linked to the larval case type and may support the independent evolution of the different larval cases. The musculature and internal sclerotizations suggest that Hyposmocoma display morphological adaptations to an atypical antiphase or tripod gait. Furthermore, the observation that H. kahamanoa has two extra trochanteral extensors and an extra trochanteral flexors suggests that extrinsic thoracic leg musculature could be informative in future studies on the gait type of Hyposmocoma. The largest morphological differences between the larval cases of two studied species suggest that the cases may be part of the secret to Hyposmocoma 's unprecedented diversity.